THE EFFECTS OF TEACHING MEDIA AND LANGUAGE ATTITUDES ON STUDENTS’ LISTENING SKILL AT STATE JUNIOR HIGH SCHOOLS IN BEKASI, WEST JAVA - Asilestari, Putri (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2018)
This research was aimed as follows : to get empirical data and analyze the effects of teaching media and language attitudes on students’ listening skill at junior high schools in Bekasi. This Reseach by using the experimental research method. The result of the research that were: 1). Teaching media give the significant effect to the student’s listening skill. Then, there was a significant difference towards student’s speaking skill in the application of audiovisual and conventional as teaching media. 2). Language attitudes give the significant effect to the student’s listening skill of the ninth grade students of SMPN 6 Bekasi, then the conclusion is that there was a significant different towards student’s listening skill who have positive and negative attitude on learning language. 3). Teaching media and language atttudes give not significant interactive effects to student’s listening skill.